Ritual as the Primordial Nexus: Bellah's Evolutionary Framework for Social Solidarity and Cultural Identity - Ridha Herdiani; Yeni Huriani; Rahimin Abdul Rahim (Jurnal Iman dan Spiritualitas, 2026)
The Ritual Roots of Society and Culture of Bellah’s work (2005) in the Handbook of the Sociology of Religion discusses ritual as the foundation of society and culture through an interdisciplinary perspective. Bellah integrates Durkheim’s (1912/1995) theory of collective effervescence, Collins (1998) on the rituals of everyday interaction, Deacon (1997) on the origins of symbolic language, and Rappaport (1999) who divides the meaning of ritual into three levels: low as information, middle as metaphor, and high as unity of self with others. Bellah argues that ritual is not just a religious practice but a basic social action that shapes solidarity, morality, and collective meaning, from human evolution to modern life, including elections and public events. A critical analysis shows the strengths of this article, namely its integration of cross-disciplinary theories, its depth of evolutionary perspectives, and its contemporary relevance. However, there are limitations, including minimal exploration of scepticism, speculative empirical examples, and a focus on the Western context. The application of Bellah’s theory to Indonesian and Sundanese culture is demonstrated through the rituals of Cokaiba Maluku, Seren Taun, traditional weddings, and angklung music, which strengthen mutual cooperation and communal identity. In the context of Islam, worship rituals such as prayer, zakat, fasting, and the pilgrimage align with Bellah’s concept, supported by Qur’anic verses such as Al-Baqarah: 43 and Al-Hujurat: 10, which foster communal solidarity amidst cultural diversity. Overall, Bellah’s theory asserts that ritual is a crucial mechanism for creating social harmony and preserving cultural identity, relevant to the challenges of globalization and secularism. The emphasis on collective meaning and solidarity makes ritual a vital instrument in maintaining social, moral, and cultural balance in contemporary society.